Seberapa perlukah kebutuhan layanan bimbingan karier ai-driven: studi pada guru bimbingan dan konseling di Indonesia - Dede Rahmat Hidayat; Lucky Nindi Riandika Marfu'i; Nira Prihatin Nufus (Jurnal Konseling dan Pendidikan, 2025)
This study investigates teachers’ needs for AI-supported integrated career guidance services. A total of 234 teachers from various regions in Indonesia participated, each with more than five years of experience teaching at junior high, senior high, or vocational schools. Using a needs-analysis questionnaire with both open- and closed-ended questions, the study found that while most teachers considered current career guidance services adequate, many expressed a strong interest in AI integration. When asked specifically about using AI in career counseling, 60.3% said it was highly necessary. Teachers also identified key features they would want in an AI-based system, including automatic interest and aptitude assessments (81.6%), student data–based career or major recommendations (81.2%), career mapping and self-development planning (69.7%), and real-time information on job markets and higher education (57.3%). These findings suggest that teachers are aware of the limitations of existing services and see significant potential in AI-driven platforms to enhance career guidance.